Eksistensi Lembaga Pengawasan Pengelolaan Keuangan Negara - Setiawan, Adam (Jurnal Hukum & Pembangunan, 2019)
Supervision of state finance management conducted by related institutions such as BPKP, DPR / DPRD, BPK and KPK aims to implement the principles of the management of state finances accordingly and in accordance with the objectives of state financial management that is to guarantee the state in order to create welfare, the right of society and finance the service to the community.